2021
DOI: 10.4193/rhin21.274
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged breastfeeding and protective effects against the development of allergic rhinitis: a systematic review and meta-analysis

Abstract: Background: There is insufficient evidence to confirm the protective effects of prolonged breastfeeding against the development of allergic rhinitis (AR). Methodology: A systematic review and meta-analysis was performed to assess the associations between prolonged breastfeeding and AR symptoms later in life. Comparisons were conducted between breastfeeding durations less than 6 months and 6 months or more and between less than 12 months and 12 months or more. Exclusive breastfeeding and nonexclusive breastfeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(146 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the microorganisms in breast milk are an important link in initiating the immune function of the infant gut and driving the colonization of intestinal microorganisms; its short-chain fatty acids, a metabolite produced by microorganisms, can affect peripheral blood T cells, especially regulatory T (Treg) cells, by inhibiting histone deacetylases to achieve immune effects [ 105 ]. The meta-analysis by Hoang et al [ 42 ] included in this study showed that either extended exclusive breastfeeding or extended non-exclusive breastfeeding (≥ 6 months) reduced the risk of AR, which is in line with the WHO recommendation that every infant should be breastfed for at least 6 months [ 102 ].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, the microorganisms in breast milk are an important link in initiating the immune function of the infant gut and driving the colonization of intestinal microorganisms; its short-chain fatty acids, a metabolite produced by microorganisms, can affect peripheral blood T cells, especially regulatory T (Treg) cells, by inhibiting histone deacetylases to achieve immune effects [ 105 ]. The meta-analysis by Hoang et al [ 42 ] included in this study showed that either extended exclusive breastfeeding or extended non-exclusive breastfeeding (≥ 6 months) reduced the risk of AR, which is in line with the WHO recommendation that every infant should be breastfed for at least 6 months [ 102 ].…”
Section: Discussionsupporting
confidence: 77%
“…A recent SRMA revealed that exclusive or non‐exclusive breastfeeding for 6 or more months may have protective effects on the development of AR up to 18 years of age 995 . A 2019 systematic review that included one cluster RCT and five prospective cohort studies examined the relationship between shorter versus longer durations of any human milk feeding (whether or not it was fed at the breast) and AR in childhood 996 .…”
Section: Risk Factors and Protective Factors For Allergic Rhinitismentioning
confidence: 99%
“…However, the limited number of included studies and substantial heterogeneity have diminished the reliability of this result. In their recent study, Hoang et al found that long-term exclusive breastfeeding did not exhibit a protective effect against AR in children, with the overall evidence quality being relatively low [16]. Despite recent original studies exploring the link between breastfeeding and the risk of AR and FA, no conclusive findings have been drawn.…”
Section: Introductionmentioning
confidence: 98%